2010
DOI: 10.1051/alr/2010032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternating feeding regimes with varying dietary phosphorus levels on growth, mineralization, phosphorus retention and loading of large rainbow trout (Oncorhynchus mykiss)

Abstract: -Excessive phosphorus (P) levels in freshwater aquaculture effluents are a major environmental problem in certain receiving water bodies. This study aimed to test an approach alternating that alternating feeding P deficient and P sufficient diets and measure P loading from rainbow trout (Oncorhynchus mykiss) culture. Three experimental practical diets consisting of P-deficient (0.4% P, P04), optimum level of P (0.6% P, P06) and P-sufficient as control diet (0.8% P, P08) were formulated. Six different feeding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…This phenomenon has also been observed in large fish. For instance, Koko et al (2010) found that changes in weight of 164 g trout fed deficient P (4.0 g kg −1 diet) and sufficient P (8.0 g kg −1 diet) over time remained similar during the initial 56 d. After this period, poor growth performance and a number of visual deficiency signs were observed, such as bone deformities in the tail regions of trout fed the P-deficient diet. However, there were no visual signs of P deficiency in the current study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This phenomenon has also been observed in large fish. For instance, Koko et al (2010) found that changes in weight of 164 g trout fed deficient P (4.0 g kg −1 diet) and sufficient P (8.0 g kg −1 diet) over time remained similar during the initial 56 d. After this period, poor growth performance and a number of visual deficiency signs were observed, such as bone deformities in the tail regions of trout fed the P-deficient diet. However, there were no visual signs of P deficiency in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…The growth performance of fish in the current study confirmed that the LP (5.4 g kg −1 diet) diet had sufficient total P to satisfy the minimum requirement for large rainbow trout. In large fish, the focus of the present study, the requirement for P is known to de crease with age because the growth rate decreases and dietary P is used mainly for maintaining meta bolic functions (Lellis et al 2004, Koko et al 2010). The P content of the LP diet was in the range of the dietary P requirement that has been reported for normal growth of rainbow trout, 4.0−6.0 g kg −1 (Ketola & Richmond 1994, Rodehutscord 1996.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Estimations based on open formulation developed by University of Guelph (Canada) and previous experiments (Koko et al., ). Plant origin phytate‐P (%) was calculated from measures on each ingredient = 0.3 for corn gluten, 0.4 for soybean, 0.4 for wheat flour and 0.09 for wheat gluten.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to remember that feeding frequency and regime could greatly influence the production of waste (e.g., solids and P and N compounds), causing peaks in its concentration [12][13][14][15] which requires increased capacity in certain treatment functions. Practicing continuous or high feeding rates, however, would result in more stable production of waste, lowering the treatment capacity requirements.…”
Section: Feed Managementmentioning
confidence: 99%